Rearranging Dispatching Layout to Minimize Dispatching Time - A. Saptari; A. Azlan; E. Mohamad (JIE Scientific Journal on Research and Application of Industrial System, 2019)
Reorganizing a layout entails a massive adjustment and thorough planning is essential before a new layout implemented. This project is to reorganize layout at dispatching area of a manufacturing industry which produces apparel accessories products. Current arrangement at the dispatching area of the company shows an interrupted flow path of activities and scattered of queuing cartons at area of activities in the dispatching line which brought to operating issues. The project aims to identify problem in current arrangement of dispatching layout, analyze the the problem and propose an alternative layout that reduces dispatching time. Time studies were applied to collect data on current performance, developing alternative arrangement, and evaluation the alternative through Witness simulation. The finding showed total dispatching time of current layout consumes 30.77 minutes to complete one dispatching job with distance travel of 162.83 meters. Better alternative layout is developed by the approach of facility planning process. Results showed the dispatching time has reduced by 32.79%, which the alternative layout only consumes 20.68 minutes to complete one dispatching job with shorter distance travel of 109.44 meters.